Edukasi Kesehatan Tentang Deteksi Dini Pencegahan Kanker Payudara Melalui Program Generasi Gemilang Cinta Sadari di SMP Negeri 1 Unter Iwes Kabaupaten Sumbawa Besar - Ninik Wahyuni; Siti Maimunah; Riska Ismawati Hakim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Breast cancer and its consequences have become a public health problem globally due to the impact of health disorders caused and the most severe impact is leading to death. Changes in diet and eating culture (fast food and lack of intake of vegetables and fruits) are one of the lifestyle changes that occur in adolescents today. Teenagers are more likely to consume foods that follow trends without looking at the nutritional status or content contained in the food. Fast food (junk food) contains a lot of dyes, preservatives, artificial flavors and how to process them by frying at high temperatures or burning. The habit of not eating less fatty foods (fruits and vegetables) and the habit of consuming red and processed meat also triggers the occurrence of tumors. One of the prevention of breast cancer is by conducting early detection of breast cancer which can be done with breast self-examination (SADARI). The purpose of this community service activity is to increase adolescents' knowledge about breast cancer and detect the early occurrence of breast cancer through breast self-examination (SADARI), This service activity involves adolescent girls in grade VIII aged 13-15 years At SMP Negeri 1 Unter Iwes, the implementation has been carried out on August 19, 2024. Service is carried out starting from preparation to evaluation. The method used in service is the method of socialization and application (application) directly in the field. The results of the evaluation showed that there was an increase in the knowledge and skills of grade VIII students after being given health education. Judging from the results of the post test, which is higher than the average pre test.